An orphan kinesin in Trypanosoma brucei regulates hook complex assembly and Golgi biogenesis - Qing Zhou; Yasuhiro Kurasawa; Huiqing Hu; Thiago Souza Onofre; Ziyin Li (mBio, 2024)
ABSTRACT Kinesins are microtubule-based motor proteins that play diverse cellular functions by regulating microtubule dynamics and intracellular transport in eukaryotes. The early branching kinetoplastid protozoan Trypanosoma brucei has an expanded repertoire of kinetoplastid-specific kinesins and orphan kinesins, many of which have unknown functions. We report here the identification of an orphan kinesin named KIN-G that plays an essential role in maintaining hook complex integrity and promoting Golgi biogenesis in T. brucei. KIN-G localizes to the distal portion of the centrin arm of the flagellum-associated hook complex through association with the centrin arm protein TbCentrin4. Knockdown of KIN-G in T. brucei disrupts the integrity of the hook complex by reducing the length of the centrin arm and eliminating the shank part of the hook complex, thereby impairing flagellum attachment zone elongation and flagellum positioning, which leads to unequal cytokinesis. KIN-G associates with Golgi through a centrin arm-localized Golgi peripheral protein named CAAP1, which maintains Golgi-centrin arm association to facilitate Golgi biogenesis. Knockdown of KIN-G impairs Golgi biogenesis by disrupting CAAP1 at the centrin arm, thereby impairing the maturation of centrin arm-associated Golgi. In vitro microtubule gliding assays demonstrate that KIN-G is a plus end-directed motor protein, and its motor activity is required for hook complex assembly and Golgi biogenesis. Together, these results identify a kinesin motor protein for promoting hook complex assembly and uncover a control mechanism for Golgi biogenesis through KIN-G-mediated maintenance of Golgi-hook complex association.IMPORTANCETrypanosoma brucei has a motile flagellum, which controls cell motility, cell morphogenesis, cell division, and cell-cell communication, and a set of cytoskeletal structures, including the hook complex and the centrin arm, associates with the flagellum. Despite the essentiality of these flagellum-associated cytoskeletal structures, their mechanistic roles and the function of their associated proteins remain poorly understood. Here, we demonstrate that the orphan kinesin KIN-G functions to promote the biogenesis of the hook complex and the Golgi apparatus. KIN-G exerts this function by mediating the association between centrin arm and Golgi through the centrin arm protein TbCentrin4 and a novel Golgi scaffold protein named CAAP1, thereby bridging the two structures and maintaining their close association to facilitate the assembly of the two structures. These findings uncover the essential involvement of a kinesin motor protein in regulating the biogenesis of the hook complex and the Golgi in trypanosomes.